Effectiveness of Gymnastic Fantasy Stories and Method of Development of Motor Musical Accompaniment Rough - Hidayatul Faizzah; Hermani Triredjeki; Susi Tentrem; Bambang Sarwono (Midwifery and Nursing Research, 2020)
Background: Physical activity by optimizing physical education in schools to improve the gross motor skills of children (Burns, 2017). Gymnastics fantasy deemed appropriate, interesting and enjoyable in accordance with the age of the child and the child's world kindergarten - a child who likes to imitate everything he sees (Aini, 2016). Gymnastics fantasy able to develop gross motor skills and social skills - emotional child. This study aims to determine the effectiveness of methods gymnastic fantasy stories as well as musical accompaniment to the development of gross motor kindergarten children in group B.Methods: This was a comparative study used pretest and posttest. The subjects were thirty children in group one and thirty children in groups of two. The object of research was a gross motor skills. Data collection techniques in this study was the observation. Data analysis technique used paired t-test and independent t-test. This study was conducted over three weeks to nine times with a population of 79 children with sampling technique sampling kuotaResults: The results used paired t-test showed Sig (2-tailed), namely that there were significant 0,001. Gymnastics fantasy stories and musical accompaniment to the development of gross motor kindergarten children in group B and the results of 0001, indicating the significance hypothesis testing more effective than the method of story accompanimentConclusion: The increase in the gross motor skills of kindergarten children can do with more teaching exploration stories and integrated gymnastic movements to the accompaniment of music